KOMPETENSI PEGAWAI, SISTEM INFORMASI MANAJEMEN DAN KEPUASAN PESERTA (JIANA ( Jurnal Ilmu Administrasi Negara ), 2018)
Employee Competency, Management Information System, ParticipantSatisfaction. This study aims to determine and analyze the influence of employee competenciesand management information systems on the satisfaction of participants in the Social SecurityService Agency (BPJS) in Pangkalan Kerinci. The study population was all participants totaling5049 people, researchers took 100 people as samples with cluster sampling technique. Datacollection methods were carried out by distributing questionnaires filled by participants. Inaddition, the researchers also conducted a literature review. Methods of data analysis usingmultiple linear regression using the help of SPSS version 18. The results showed that partially thecompetence of employees significantly influence participants' satisfaction. While the managementinformation system has a positive and significant effect on the satisfaction of BPJS participants inPangkalan Kerinci. Simultaneously employee competencies and management information systemshave a positive and significant effect on the satisfaction of BPJS participants in Pangkalan Kerinci.The coefficient of determination of employee competencies and management information systemson participant satisfaction was 77.4%. While the remaining 26.6% is an indication of other factorsnot examined in this study.